Pengembangan Bahan Ajar Matematika Berbasis Realistic Mathematics Education untuk Menumbuhkan Kemampuan Literasi Matematika pada Siswa Kelas IV SDN Bengkulu Utara - Febriansyah Nur Arifin; Victoria Karjiyati; Neza Agusdianita (JURIDIKDAS, 2022)
This study aims to produce mathematics teaching materials using the Realistic Mathematics Education (RME) approach to foster mathematical literacy skills in fourth grade elementary school students that are feasible and effective to use. This research method is the Research and Development (R&D) method the modifed 4D model. However, this research is only at the development stage, because the COVID-19 situation has not improved. Validation is carried out by material, design, and linguist experts. The teaching materials developed were graded by 3 teachers of elementary school in north Bengkulu and tested on a limited basis in 2 elementary schools. The data analysis technique used descriptive qualitative and quantitative analysis. The results of expert validation were tested with an interrater reliability test to see the agreement between raters. This research produces RME-based mathematics teaching materials to foster mathematical literacy skills on the circumference and area of flat shapes in fourth grade elementary school students. The results of the validation of material experts get the score of 88.9 in the very good category, linguists get the score of 87.7 in the very good category, design experts get the score of 86.6 in the very good category, and get comments that the depth of the description is in accordance with the level of student development, the language used is communicative, fosters a sense of fun and stimulates students to answer questions, the overall illustrations and letters used are simple, harmonious and attractive. The teacher's response got an average score of 91.3 with a very good category. The results of the limited trial got an average score of 87.7 with a very good category. The product of developing mathematics teaching materials based on Realistic Mathematics Education to foster mathematical literacy skills is very good for use by fourth grade elementary school students.